Censor Nikolay Ratynsky’s Role in Russian Journalism of the Second Half of the 19th Century - Mazalevskiy, Dmitriy (Slavica, 2018)
Recently, the political climate in Russia has caused the question of censorship to becomean increasingly relevant issue, the history of which is necessary to explore and understand.The prevailing view regarding censorship is that it is a tool used to suppress the freedom ofspeech by stifling the writer’s thoughts. However, there were some eminent censors such asthe poet Fyodor Tyutchev and the writer Ivan Goncharov. In this regard, it has become commontto consider censorship isolated from any moral categories and interpret g it only as aprofessional activity. In this context, the work of the censor Nikolai Ratynsky is of particularinterest to us. Until now, little has been published on his influence as a censor on the writersof his time on the high professional level of his work in this capacity. Most of the correctionsRatynsky made were valid and justified by the political situation in the Russian Empire. Hehimself is further proof that, along with Tyutchev and Goncharov, there were honorable andqualified men among the censors of the time. All this allows us to claim that it is necessaryto objectively consider and study the work of censors and ignor preconceptions and stereotypesthat are usually associated with the word censor.